PERANCANGAN GAME EDUKASI MERAKIT PESAWAT MENGGUNAKAN MACROMEDIA FLASH 8.0 (Information Technology and Telematics, 2013)
This educational game will train the child's motor development, training and concentration by this game the chilcan recognize the shape and type of aircraft. Macromedia Flash 8 is the latest version of the program from the previouversion of the Macromedia Flash MX. This latest version has many changes in appearance, Filters, Blend Modes and othefacilities. Games or educational games using flash assemble this aircraft intended to be able to play while learning trecognize and assemble paswat. Game assemble aircraft parts on planes or construct This game tells the precision idrafting a series of aircraft with aircraft types and difficulty levels form different planes, and there is a time limit iassembling aircraft.To design an application program Assemble Aircraft Cyber Games, the writer uses Macromedia Flas8.0 due to make a simple animation or game using Macromedia Flash 8, the required script is not as complicated as otheprogramming language.  Keywords: Educational Games, Macromedia Flash 8.0.